Filosofia das imagens na escola: uma alternativa para filosofar com crianças - Mousquer, Elenir de Fátima Cazzarotto (2004)
The study proposes itself a relevance and viability analysis of the insertion of Philosophy in the educational proposal, to the level of basic education. In the search of understanding that is configured in an emancipator process by the vies of the aesthetic experience. The discussion of the subject of the Philosophy of images as pedagogical-didactical alternative to philosophize with children in school, has as basic theoretical contributions the Program Philosophy for Children, by Matthew Lipman, and the Theory of Communicative Action by Jürgen Habermas. Philosophy has been permitting us to unveil the paradigms for education, in the transition to the post-modern society, in the presence of emerging necessities in the pedagogical action, with the shift from the conscience philosophy to the language philosophy, in which is accented the dialogical and communicative character of reason. Through the hermeneutic reading exercise, there is the purpose of analyzing some significant moments referring to the emergence of the infancy and its different images, searching the philosophical understanding in the global context, always noticing the specificity of our country. It is believed, that Philosophy through images may resignify the process of insertion of Philosophy in the schools and redimensionate the cultural formation dynamic, renewing the discussion about its teaching, departing from the referential of aesthetic images used in the language. In the present context, the images propose themselves as an access channel to knowledge, and in a second moment as a didactic resource. In the knowledge construction it is fundamental a deeper and more complete reflexion of the educative activity, due to the possibility of interpretation of the tensions that occur in the ambit of education, linking to this aspect a cognitive competence development theory and the implications of a communicative rationality in the pedagogical praxis.